Perspektif Pendeta Gereja Punguan Kristen Batak tentang Pelayanan Ramah Disabilitas bagi Jemaat (International Forum of Researchers and Lecturers, 2025)
This study aims to understand the perspectives of pastors from the Punguan Kristen Batak Church (GPKB) regarding disability-friendly services for congregants. As a faith community, the church has a significant responsibility to create an inclusive environment where every member, including those with disabilities, is accepted and served equally. People with disabilities are seen not only as part of human diversity but also as part of the whole body of Christ, and therefore, their service must be prioritized in church life. This research uses a qualitative descriptive analytical approach, with data collected through in-depth interviews with six pastors from GPKB districts in Indonesia to explore theological understanding, practical experience, and challenges in serving congregants with disabilities. Data analysis was conducted thematically to identify patterns of views, service practices, and obstacles that arise. The results show that 84% of pastors have a positive perspective on inclusive service and support congregants with disabilities. However, the study also found challenges such as inadequate physical facilities, minimal service strategies, and limited theological understanding of disabilities. In conclusion, a paradigm shift, capacity building for pastors, and ongoing institutional support are needed to create an inclusive and disability-friendly church.